Judicial protection of the rights of the victim (bank-creditor) after the conclusion of the agreement of assignment of the right (requirements) in the conditions of the intentional bankruptcy of the debtor. - Y. Truntsevsky (Правоприменение)
The subject of analysis in the paper is Russian insolvency legislation? As well as rules ofRussian Criminal Code about insolvency crimes.The purpose of the article is to analyze methods of the judicial protection of the rights ofthe victim (creditor-bank) after the conclusion of the contract of cession of rights (claims)in the context of deliberate bankruptcy of the debtor.The methodology of research includes: analysis, synthesis, induction, deduction, survey,and statistical method.The results, scope of application. Intentional bankruptcy (Art. 196 of the Russian CriminalCode) violates the legitimate property interests of creditors. In particular, the Bank has theright to appeal to law enforcement agencies with a statement about criminal acts committedagainst the Bank that caused damage to the Bank. The creditor has the right to applyfor recognition as an injured person. Such a creditor is harmed by a crime. In the event thatthe Bank deliberately bankruptcy of the debtor harmed, and there is a causal relationshipbetween such actions and the socially dangerous consequences that have occurred, then,as follows from Part 1 of Art. 44 of the Code of Criminal Procedure, this circumstance is aprerequisite for the recognition of the Bank as a civil plaintiff. Such a bank has the right todeclare in the criminal case a civil claim for damages to the bank. The purpose of this articleis to provide judicial protection of the rights of the victim (creditor bank) after concludingthe contract of assignment of the right (claims) in the circumstances of the debtor's deliberatebankruptcy. The research methods are: analysis, synthesis, induction, deduction,questioning and statistical method. The conclusion is drawn that the assignment of claimsunder a civil law contract is not grounds for refusing to recognize the Bank as a victim anda civil plaintiff in a criminal case under Art. 196 of the Criminal Code.Conclusions. The assignment of claims under civil contract is not a ground for refusingrecognition the Bank as the victim and civil plaintiff in a criminal case under Arti. 196 of theCriminal Code.